MICROENCAPSULATION: A REVIEW ON POLYMERS AND CORRELATION WITH BCS CLASSIFICATION OF DRUGS - SHREYA MUKHERJI,; VIVEK NALAWADE, (International Journal of Pharma and Bio Sciences, 2015)
Microencapsulation has evolved in the last decade to become a frontrunner in the delivery of drugs. With the ever increasing drugs being synthesized, the number of polymers to coat it and help with their stability has also increased. This review describes the need for this process and the different aspects of the process of Microencapsulation and provides a glimpse into the various techniques of this process and the variety of polymers in use. This review comprises of a tabulation of a literary survey of the researches on microencapsulation of the various drugs, their BCS classification and the polymers used to encapsulate the drugs.This tabulation aids in establishing a correlation between the BCS classification of the drug and the polymer used to serve the purpose of microencapsulation.